Przezwisko w komunikacji wewnątrzrodzinnej = A nickname inside the family communication - Idzikowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to discuss family nicknames treated as informal anthroponyms, children`s descriptions created and used in the family circle in the next of kin communication. Taking into consideration the origin of the nickname, three following types have been distinguished: 1) anthroponyms motivated by the name of its owner, 2) anthroponyms motivated by another proper names, 3) anthroponyms motivated by the appellative names.
Keywords: przezwisko; nazwa własna; język familijny; komunikacja wewnątrzrodzinna; forum internetowe; nickname; proper name; family language; inside the family communication; Internet forum